Assay of Bacteriorhodopsin Activity and Structure on Polycarbonate Surface by Spin Coating Method and Photochemical Activity Analysis - Nazarian, Niloofar; Molai Rad, Ahmad; Pooladi, Mehdi; Taghizadeh, Bita (Archives of Advances in Biosciences, 2019)
Introduction: Protein-based memory is a novel technology that employs proteins ability to participate in electronic processes. Bacteriorhodopsin (BR) is a membranous proton pump that it’s applications in bio-molecular electronic devices has been widely studied. The results of this research show that BR bounded to modified polycarbonate surface has higher activity for spin coating method. Materials and Methods: In an in-vitro study, BR-containing polymer matrix of polyvinyl alcohol and gelatin with different w/v ratios was prepared. Spectroscopic and enzyme activity analysis was performed and the optimized concentration for BR-containing films was determined to be 3.2 mg/ml. BR-polymer was then immobilized on the polycarbonate surface with spin coating method and AFM microscopy was used to characterize BR-coated polycarbonate. Results: Based on the obtained results we conclude that polymer concentrations below 1% significantly reduced BR activity levels. A280/A570 of 3.64 for 3.2 mg/ml BR solution and 4.97 for BR in 1% polymer confirmed the quality prepared film. AFM study of BR-coated polycarbonate surface revealed the overall thickness of 25nm, indicating that we were able to prepare a surface with suitable thickness for nano electronic devices Conclusion: The results of this research show that BR bounded to modified polycarbonate surface has higher activity for spin coating method.